Prevalence of Depression and Its Associated Risk Factors in the Primary Care Setting in Kuantan - Md Aris, Mohd Aznan; Halim, Noor Azlina; Musa, Ramli (ScienceDomain International, 2014)
Aims: To determine the prevalence of depression and its associated risk factors among adults attending primary care clinics in Kuantan. Study Design: Cross-sectional. Place and Duration of Study: Public primary care clinics in Kuantan, Pahang between July 2008 and September 2008. Methodology: The respondents were selected through simple random sampling among adult attendees of public primary care clinics in Kuantan, Pahang. The Malay validated version of Brief Patient Health Questionnaire (PHQ-9) was administered as a screening tool for depression. A part from social-demographic data, we also obtained information on medical illnesses and history of substances abuse. A total of 502 patients were approached and 452 respondents agreed to be enrolled in the study. Results: The study found that 10.6 percent of them were having depression, 0.7 percent had history of drug abuse, 2.4 percent had consumed alcohol and 21.7 percent suffered from chronic illness. The study revealed that depression was significantly associated with chronic illness (OR: 2.702, 95% CI [1.409, 5.184]), and drug abuse (OR: 39.152, 95% CI[1.662, 992.291]). Conclusion: Adults with history of drug abuse or those who suffered from chronic illnesses have higher risk of suffering from depression and need greater attention from primary care providers.